Ways of development of the relationship between farms from collective enterprises - Shinet, G.G.; Andarova, R.K.; Zhadigerova, G.A.; Narkulova Sh. А. (BUKETOV BUSINESS REVIEW, 2019)
The article considers the activities of households in the agricultural sector of the Republic of Kazakhstan and its share in the production of modern agricultural products. The article describes the cooperative as a special economic unit of agriculture, combining and interacting human and material factors. The level and features of development of cooperative abroad are widely described. And also cooperation as cooperation of personal subsidiary farms with large agrarian formation for dynamic development of economies of the population is considered. The article focuses on the legal and economic prerequisites for the development of households as an equal form of agricultural production, its transformation into an independent peasant economy, as an equal participant in agricultural production. The importance and necessity of bilateral mutually beneficial functions of cooperation between private farms and agricultural enterprises is substantiated. The interests of cooperation between agricultural enterprises and private households are clearly presented in the form of a scheme. Everyday economic and organizational problems of households, which are directly related to their effective development, along with social problems, were also studied. A number of problems were considered, such as lack of integration between agricultural enterprises and households; low level of legal and social status of households; lack of material and technical equipment, fertilizers, multiple livestock and agricultural plant; feed for livestock in private farms to increase the number of livestock and slaughter cattle in the meat industry.